(untitled) (Kriminalističke teme, 2022)
The aim of the research is to examine the impact of the COVID-19 pandemic on the occurrence and magnitude of mental health consequences among students at the University of Sarajevo, which manifest themselves in certain types and levels of psychological distress, as well as to examine various aspects of general mental functioning that are particularly important in an online learning and teaching environment. The research was conducted in July 2021 on a sample of 3439 students at the University of Sarajevo. The following measurement instruments were used: The Depression, Anxiety and Stress Scale (DASS-21), a Stress Coping Strategies Inventory and a Sociodemographic Variables Questionnaire. The results have shown that depression, anxiety and stress were present among students at levels which require additional interventions. Symptoms are significantly more present among female students than among male students. The differences tested between students of distinct faculties indicate that arts students have the highest values of depression, followed by students studying humanities, while social sciences students show the lowest values. The results showed that positive coping with stress is a protective factor for the symptoms of anxiety, depression and stress, while negative coping style is a risk factor for students' mental health. The obtained results suggest that the pandemic has a significant psychological impact on students that require interventions in improving their mental health.